Distribuição espacial e manejo de Tibraca limbativentris Stal (Hemiptera: Pentatomidae) no Estado do Maranhão - Costa, Elizabeth Araújo (2019)
The objective of this research was to describe the spatial distribution of Tibraca limbativentris in rice culture and in young babassu palms; to study the reproductive system of females in diapause of the stink bug in young babassu palms and evaluate the use of entomopathogenic fungi in the biological control of this pest. To describe the spatial distribution, monthly sampling of the stink bug population was carried out in rice tussocks and young babassu plants in areas of family farmers in the municipality of São Vicente Ferrer - MA. At all sampled points the UTM coordinates were obtained with a GPS device. After marking the points, the rice tussocks and babassu plants were inspected and the number of insects counted. From the geostatistical analysis it was possible to construct the kriging maps and estimate the spatial dependence of stink bugs. The females collected in the young babassu palms were dissected in the laboratory, to verify the maturity of the reproductive system by presence of oocytes in the ovaries, and possible diapause of T. limbativentris in this alternative host. For microbial control of rice stink bug in rice fields, were used isolates of the entomopathogenic fungi Metarhizium anisopliae (MGSS 189 and MGSS 192) and Beauveria bassiana (MGSS 87) and commercial products Opala ® (M. anisopliae) and Granada ® (B. bassiana). The isolates were applied in conidia suspension and in rice grains covered with fungal products at concentration of 1x107. The products Opala® and Granada® were applied in dosages 0.75 and 5.5 kg p.c./ha, respectively, and distributed manually in the granulated (Opala®) and wettable powder (Granada®) formulations. The design was randomized complete blocks with 6 treatments and 4 replications. Evaluations of the number of live and dead specimens of T. limbativentris were performed before the applications and 15 days after the fungal application. Were collected 1638 T. limbativentris adults, 1584 registered in rice tussocks and 54 from babassu palm. The spatial distribution of the stink bug was aggregated in the rice areas, and the exponential model was the one that best fitted this host. In the babassu palms the pest was randomly distributed, not fitting to any statistical model (pure nugget effect). Oocyte absence was observed and the presence of abdominal cavity body fat were observed in females of T. limbativentris, which characterizes the immature reproductive organ and females entering the diapause period. Treatments with entomopathogenic fungi had the potential to control T. limbativentris, after 15 days of application there was a population reduction. The isolates and commercial products of M. anisopliae and B. bassiana were effective in controlling nymphs and adults of T. limbrativentris.